The returned [large type] - Mott, Jason (Mott, Jason. Returned, 2013)
Harold and Lucille Hargrave's lives have been both joyful and sorrowful in the decades since their only son, Jacob, died tragically at his eighth birthday party in 1966. In their old age they've settled comfortably into life without him, their wounds tempered through the grace of time ... Until one day Jacob mysteriously appears on their doorstep -- flesh and blood, their sweet, precocious child, still eight years old. All over the world people's loved ones are returning from beyond. No one knows how or why this is happening, whether it's a miracle or a sign of the end. Not even Harold and Lucille can agree on whether the boy is real or a wondrous imitation, but one thing they know for sure: he's their son. As chaos erupts around the globe, the newly reunited Hargrave family finds itself at the center of a community on the brink of collapse, forced to navigate a mysterious new reality and a conflict that threatens to unravel the very meaning of what it is to be human.